2014
DOI: 10.2147/copd.s61265
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the COPD Assessment Test score and airflow limitation in Japan in patients aged over 40 years with a smoking history

Abstract: BackgroundA large number of chronic obstructive pulmonary disease (COPD) patients in Japan remain undiagnosed, primarily due to the underuse of spirometry. Two studies were conducted to see whether the COPD Assessment Test (CAT) in primary care has the potential to identify those patients who need spirometry for a diagnosis of COPD and to determine whether patients with cardiovascular disease had airflow limitation, which could be detected by CAT.Materials and methodsTwo multicenter, noninterventional, prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…Several studies have reported the CAT scores as a screening tool for COPD in a general population. 14 , 22 However, this study showed that the elevated CAT scores are not disease specific, but the patterns of elevated CAT components might be more useful to characterize these diseases. Elevated exertional dyspnea score compared to other components was observed in patients with COPD and ACOS, suggesting the presence of persistent airflow limitation.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Several studies have reported the CAT scores as a screening tool for COPD in a general population. 14 , 22 However, this study showed that the elevated CAT scores are not disease specific, but the patterns of elevated CAT components might be more useful to characterize these diseases. Elevated exertional dyspnea score compared to other components was observed in patients with COPD and ACOS, suggesting the presence of persistent airflow limitation.…”
Section: Discussionmentioning
confidence: 75%
“… 12 , 13 The CAT score has been shown to be useful to identify subjects who require spirometry for the diagnosis of airflow limitation. 14 In contrast to the asthma control test (ACT), which asks about asthma-specific symptoms and reliever use, 15 the CAT score consists of eight nonspecific questions about disease impacts.…”
Section: Introductionmentioning
confidence: 99%
“…The greater predominance of older Japanese male COPD patients is typical of other Japanese studies in clinical settings. 26 28 However, the data from the Japanese population in the current study show that, despite the exclusion of patients with asthma, a proportion of patients have high eosinophil counts. Of note, one included study (the Japanese COSMOS-J trial; Table S1 ), 18 of 400 patients with COPD, did not exclude patients with asthma.…”
Section: Discussionmentioning
confidence: 52%
“…Pothirat et al 14 showed change in CAT score was valid to detect acute exacerbation. Yoshimoto et al 15 suggested CAT score was related with airflow limitation. Sarioglu et al 16 demonstrated CAT score was associated with systemic inflammatory marker.…”
Section: Discussionmentioning
confidence: 99%